THE USE OF GROUP TESTS TO PROMOTE COLLABORATION AND LEARNING: DO THEY WORK? - Gilbride, Kimberley Ann (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2020)
The research was carried out to determine whether the use of group tests for undergraduate science students to augment lecture material in a second-year core course in microbiology would improve the retention of material on a subsequent regular mid-term/final exam. On three separate occasions, the students were asked to complete short multiple-choice tests individually and then were asked to get together in groups of 4 to re-answer the same questions. The discussions they had in the groups improved their individual marks by 10.9% in the first test, 14.5% in the second test and 20.9% in the third test. Overall, the class average was 2.5% better than the previous year. The majority of the students indicated that the group tests improved their understanding and helped them to learn the lecture material.